2005
DOI: 10.1152/ajpregu.00565.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense responses to sleep loss and sleep recovery

Abstract: Sleep deprivation in humans is widely believed to impair health, and sleep is thought to have powerful restorative properties. The specific physical and biochemical factors and processes mediating these outcomes, however, are poorly elucidated. Sleep deprivation in the animal model produces a condition that eventually becomes highly lethal, lacks specific localization, and is reversible with sleep, implying mediation by a biochemical abnormality. Metabolic and immunological consequences of sleep deprivation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 56 publications
4
128
0
Order By: Relevance
“…In the liver tissue, GSH-Px also can accelerate the removal of free radicals to reduce liver injury. Everson et al found that GSH-Px activity in the liver was significantly lower than that in the control group after 5 days continuous SD [14]. Our experimental results showed that the activity of SOD and GSH-Px in the liver of the rats in the group SD was significantly lower than that in the control group, indicating that sleep deprivation could reduce the antioxidant stress ability.…”
Section: Discussionmentioning
confidence: 40%
“…In the liver tissue, GSH-Px also can accelerate the removal of free radicals to reduce liver injury. Everson et al found that GSH-Px activity in the liver was significantly lower than that in the control group after 5 days continuous SD [14]. Our experimental results showed that the activity of SOD and GSH-Px in the liver of the rats in the group SD was significantly lower than that in the control group, indicating that sleep deprivation could reduce the antioxidant stress ability.…”
Section: Discussionmentioning
confidence: 40%
“…Sleep deprivation in rats was produced by the Bergmann-Rechtschaffen method (7, 24) for 5 or 10 days, which was tolerated and produced hyperphagia and a negative energy balance, as already reported (19). Two freely moving rats were studied at a time.…”
Section: Methodsmentioning
confidence: 99%
“…The 48-h period of measurement was based on previous findings of a return to near basal levels of energy expenditure (18) and normalization of the liver content of glutathione and catalase activity, which are principal free radical scavengers (19). Rats in the sleep recovery groups were injected 6 h before tissue harvest with 25 to 50 mg of bromodeoxyuridine (BrdU)/kg body wt for further studies of cell renewal.…”
Section: Methodsmentioning
confidence: 99%
“…To produce chronic sleep restriction, the disk was rotated for 6 s according to a pattern of disk rotations that had reliably produced reduced and highly fragmented sleep under acute conditions (23,26). In these prior studies, the housing platform had been rotated for 6 s each time sleep onset was detected in a rat to be totally deprived of sleep, which reduced and fragmented the sleep of a paired rat housed on the same platform.…”
Section: Animals and Environmental Conditionsmentioning
confidence: 99%
“…Each sleep-restriction period lasted 10 days, which is known to be tolerated in rats under acute sleep-loss conditions (2,18,20,21,24,28,53,55). Each intervening period of sleep ad libitum lasted 2 days, which previously has been shown to normalize energy expenditure and antioxidant parameters in totally sleepdeprived rats (22,23). The 10-day sleep-restriction and 2-day sleep-recuperation periods were repeated consecutively six times during 10 wk, which is a duration of 72 days determined a priori.…”
mentioning
confidence: 99%